Identification of antigen-specific serological cross-reactivity among survivors of Crimean-Congo Haemorrhagic fever - Rangunwala, Azeeza (University of the Free State, 2013)
Abstract not available
Dissertation (M.Sc. (Medical Microbiology and Virology))--University of the Free State, 2013
Keywords: Hemorrhagic fever; Virus diseases -- South Africa; Tick-borne diseases -- South Africa; Cross-reactions (Immunology); Antigens; Serology